Spin-off as an indicator of regional innovation network development - Konstantin Ivanovich Grasmik (Triple Helix, 2015)
It is not easy to design an appropriate indicator of network collaboration that is relevant and comparable to all regions of the Russian Federation. This is a challenge because the creation of high-tech start-ups requires the cooperation of various and heterogeneous stakeholders: inventor, entrepreneur, investor, and the university. Accordingly, the purpose of this paper is to test the following hypothesis: the greater the number of viable spin-offs in the region, the higher the level of innovative activity of the region.
Keywords: O17; O31; O32; 330; Entrepreneurial university; Innovation network; Regional innovation system; Spin-off